2014
DOI: 10.1128/aac.03169-14
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin Induces Hydroxyl Radical Formation in Mycobacterium tuberculosis

Abstract: The antituberculosis (anti-TB) drug rifampin (RIF) binds to the beta subunit of the RNA polymerase (RpoB) of Mycobacterium tuberculosis, but the bactericidal responses triggered after target interaction are not known. To evaluate whether RIF induced an oxidative burst, lysates of RIF-treated M. tuberculosis were tested for determination of reactive oxygen species (ROS) by the electron paramagnetic resonance (EPR) technique using 1-hydroxy-3-carboxy-pyrrolidine (CPH) and 5,5-dimethyl-1-pyrrolidine-N-oxide (DMPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 34 publications
(81 reference statements)
7
71
1
Order By: Relevance
“…Gram-negative and Gram-positive bacteria that were exposed to lethal concentrations of antibiotics have been found to have a high degree of oxidative stress due to elevated levels of ROS (68,(93)(94)(95)(96)(97). M. tuberculosis, which was exposed to 8 g/ml of RIF but only up to 3 days (pertaining only to the early part of killing phase) in vitro, showed generation of hydroxyl radical, the levels of which increased with the increase in RIF concentration (98). However, our study involving prolonged and continued exposure to RIF showed that the levels of hydroxyl radical generation were steadily increasing during the killing phase, reaching significantly high levels in the RIF persistence phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative and Gram-positive bacteria that were exposed to lethal concentrations of antibiotics have been found to have a high degree of oxidative stress due to elevated levels of ROS (68,(93)(94)(95)(96)(97). M. tuberculosis, which was exposed to 8 g/ml of RIF but only up to 3 days (pertaining only to the early part of killing phase) in vitro, showed generation of hydroxyl radical, the levels of which increased with the increase in RIF concentration (98). However, our study involving prolonged and continued exposure to RIF showed that the levels of hydroxyl radical generation were steadily increasing during the killing phase, reaching significantly high levels in the RIF persistence phase.…”
Section: Discussionmentioning
confidence: 99%
“…The powdered cell lysate was resuspended in 200 l of 100 mM sodium acetate (pH 5.2) and centrifuged at 12,000 ϫ g for 5 min at room temperature. The supernatant (180 l) was then mixed with 20 l of 1 M DMPO to achieve a 100 mM final concentration (98). Samples were immediately loaded into an aqueous flat cell (ES-LC12), and a reading was taken in a JEOL JES-X3 ESR spectrometer exactly 2 min after the addition of DMPO using the following parameters: X-band frequency, 9428.401 (MHz); power, 4.00 (mW), field center, 337.275 (mT); sweep time, 2.0 (min).…”
Section: Methodsmentioning
confidence: 99%
“…In Mtb , RIF inhibits the beta subunit of RNA polymerase (RpoB) encoded by the rpoB gene . The cellular responses to RIF involve generation of ROS, mainly the hydroxyl radical . As elesclomol through its copper chelate also generates oxidative stress, this may explain the observed synergism.…”
Section: Discussionmentioning
confidence: 99%
“…After binding to its target, RIF produces superoxide radical anion, which further mediates metal‐dependent generation of hydroxyl radical, confirmed by electron paramagnetic resonance (EPR). This is in‐part, responsible for its antimycobacterial activity . Thus, this illustrates the potential for design and development of redox‐based drugs against TB.…”
Section: Introductionmentioning
confidence: 93%